DEVELOPMENT STUDY FRAMEWORK INDICATOR OF NEED ASSESSMENT INSTRUMENT GUIDANCE AND COUNSELING USING ISLAMIC APPROACH - Karyono Ibnu Ahmad (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
This research aims to develop indicator framework of need analysis Islamic guidance and counseling. Method used in this research base on qualitative research approach. This research using qualitative research under the consideration that this research will reconstructed point of view of new conceptualization by conducting literary study base on practice reflection become counseling with judgment in Indonesia Language expert and guidance and counseling expert but it isn’t until validity test and item reliability yet. The result of this research show competence aspect and accomplishment indicator in instrument using Al’Quran sura Lukman verse 12-19, because this sura known as base of Islamic education value and sura Al Furqaan verse 63-74